1987
DOI: 10.1159/000174186
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants as Antiarrhythmic Drugs

Abstract: Experiments on rats and rabbits using models of arrhythmias induced by vasopressin, epinephrine, strophanthin, and CaCl2 showed that antioxidants derived from 1,4-dihydropyridines, dibunol, and α-tocopherol possessed antiarrhythmic effects. Administration of these antioxidants decreased the occurrence of extrasystoles, disturbances of atrioventricular conductivity and ventricular fibrillation. These drugs also prevented changes in membrane phospholipid composition, inhibited activation of peroxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 6 publications
(6 reference statements)
0
6
0
Order By: Relevance
“…Diludine 3, ionol 30 and some other antioxidants, which prevented and protected mitochondria against swelling and disintegration (caused either by AsA induced lipid peroxidation, or exogenic phospholipase A 2 or products of their enzymatic cleavage reaction Ð salts of unsaturated FFAs) can act as antiischaemic agents, if used in vivo prophylactically, preventing heart, kidney and other organs from ischaemic and reperfusion lesions. 10,11,34,35,37 The eect was dependent on dose, time of application and introduction mode. Using antioxidants, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Diludine 3, ionol 30 and some other antioxidants, which prevented and protected mitochondria against swelling and disintegration (caused either by AsA induced lipid peroxidation, or exogenic phospholipase A 2 or products of their enzymatic cleavage reaction Ð salts of unsaturated FFAs) can act as antiischaemic agents, if used in vivo prophylactically, preventing heart, kidney and other organs from ischaemic and reperfusion lesions. 10,11,34,35,37 The eect was dependent on dose, time of application and introduction mode. Using antioxidants, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…More importantly, our data demonstrate that ROS mediates the inhibitory effect of ceramide on I HERG and antioxidants can prevent the I HERG depression. This explains at least partly the benefits of antioxidants in preventing and suppressing arrhythmias in ischemic myocardium and failing hearts [46,47]. Indeed, Tsuji et al [25] showed I Kr , measured as E-4031-sensitive tail current, to be ∼36% smaller in rabbits with ventricular tachypacing-induced CHF than in healthy rabbits.…”
Section: Role Of Reactive Oxygen Species (Ros) In I Herg Modulation Bmentioning
confidence: 99%
“…The findings of these studies, together with the concept that free radicals may contribute to the genesis of reperfusion-induced arrhythmias, gained support from other investigations using a wide variety of interventions, including coenzyme Q10 [40], and several species, including the dog [36,[41][42][43][44][45][46][47][48]. Support also came from a number of electrophysiologic studies [49][50][51][52], again in several species.…”
Section: Reperfusion-induced Arrhythmiasmentioning
confidence: 85%